NEO 2 - Molišová, Kateřina (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Dipolomová práce NEO 2 je environmentálně zaměřeným, procesuálním projektem, který vychází z problematiky tzv. kůrovcové kalamity. Zabývá se otázkou personifikace mimolidského života. Využívá zkušenosti s materiály, jejich manipulací a opracováním.

Diploma thesis is an environmentally and process oriented project which is based on the issue of the so-called bark beetle calamity. It deals with the personification of non-human life. It uses experience with materials, their handling and processing.
NEO 2
Keywords: kúrovcová kalamita; environmentalismus; site-specific; personifikace.; bark beetle calamity; environmentalism; site-specific; personification.